Stretchable electromagnetic fibers for self-powered mechanical sensing. (September 2020) - Du, Zhuolin; Ai, Jingwei; Zhang, Xuan; Ma, Zheng; Wu, Zhenhua; Chen, Dezhi; Tao, Guangming; Su, Bin
Graphical abstract: Highlights: Stretchable electromagnetic fibers with a self-powered sensing capacity are proposed. Sensing fundamental mechanisms are investigated by the Maxwell simulation. Diverse parameters to improve the self-powered capacity are discussed. Promising applications of robotic self-perception are demonstrated. Abstract: Fiber based sensors may enable a new class of wearable electronics due to their high flexibility, great breathability and direct integration into daily clothes, but progress is hindered by the power supply model that greatly restricts their duration and user experiences. Here we report the fabrication of stretchable electromagnetic fibers that can recognize mechanical forces with a self-powered feature. Conductive wires were twined outside stretchable magnetic fibers, enabling relative movements between magnetic and conductive fibers during cycles of stretching/recovery. Therefore, those electromagnetic fibers can sense the applied forces based on electromagnetic induction effect. Tuning fabrication parameters, such as magnetic powder content, fiber diameter and the number of twined conductive wires, can improve the performance of electromagnetic fibers. Owing to self-powered sensing capacity, flexibility and long-term durability, such electromagnetic fibers were attached onto fiver fingers of a robotic hand to endow the robot with a self-perception capacity. Our study employs a scalable wet-spinning method to prepare electromagnetic fibers and illustrates the critical design concept to obtain optimized electromagnetic performances of those fibers, which would facilitate further development of fibertronics and wearable electronics.